The southern Levant under Assyrian domination - Aster, Shawn Zelig; Faust, Avi (Eisenbrauns, 2018)
"Presents a series of studies that address various aspects of Assyrian rule in the southern Levant and its consequences, as well as life under Assyrian hegemony, and the sources available for such studies"--Provided by publisher